2009
DOI: 10.1111/j.1440-1681.2009.05248.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐inflammatory modification of colonic afferent mechanosensitivity

Abstract: 1. The present review discusses interactions between the immune and nervous systems in post-infectious irritable bowel syndrome (PI-IBS). 2. Visceral pain is the single symptom that most affects the quality of life of patients with irritable bowel syndrome (IBS), yet it is the least successfully managed. An underlying hypersensitivity of colonic afferents to mechanical stimuli has long been implicated in visceral pain in IBS, but little more is known of the physiological aetiology. 3. The PI-IBS patients are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 79 publications
1
52
0
Order By: Relevance
“…While the exact mechanisms are unknown, current evidence suggests a pathologic crosstalk between the immune and peripheral nervous systems through cytokines and other inflammatory mediators that promote afferent sensitization as a probable cause for the development of postinflammatory visceral hypersensitivity (reviewed by [43,44]). In support of a central sensitization mechanism, Zhou and colleges [45] demonstrated that rats with post-inflammatory colonic hypersensitivity at 16 weeks following a TNBS enema have increased expression splice variants of the NR1 subunit of the N-methyl-D-aspartic acid (NMDA) receptor in the superficial lamina of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact mechanisms are unknown, current evidence suggests a pathologic crosstalk between the immune and peripheral nervous systems through cytokines and other inflammatory mediators that promote afferent sensitization as a probable cause for the development of postinflammatory visceral hypersensitivity (reviewed by [43,44]). In support of a central sensitization mechanism, Zhou and colleges [45] demonstrated that rats with post-inflammatory colonic hypersensitivity at 16 weeks following a TNBS enema have increased expression splice variants of the NR1 subunit of the N-methyl-D-aspartic acid (NMDA) receptor in the superficial lamina of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…This colitis is transient, peaking several days after administration and then spontaneously healing such that by 28 days following administration the histology of the colon and myeloperoxidase levels do not differ from untreated animals (Hughes et al, 2009a;Hughes et al, 2009b;Krauter et al, 2007;Qin et al, 2011). However, colonic afferent nerves remain sensitized to distension long after the mucosa heals, which models aspects of the chronic visceral hypersensitivity (CVH) experienced by IBS patients (Gschossmann et al, 2004;Hughes et al, 2009a;Hughes et al, 2009b). In this model muscular / mucosal afferents are sensitized to mucosal stroking but not circular stretch, and the sensitization observed is relatively modest compared to hypersensitivity displayed by high-threshold afferents (Hughes et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…They also express putative nociceptive channels, including members of the Transient Receptor Potential (TRPV1, TRPA1) and Acid Sensing Ion Channel 6 (ASIC3) families, implying they act as intensity encoders and modulate the sensory processing of pain (Brierley et al, 2009;Brookes et al, 2013;Gebhart, 2000;Jones et al, 2005). Immune derived mediators are known to excite viscerosensory nerves and have previously been implicated in the heightened sensitivity to distension of the colo-rectum experienced by IBS patients (Hughes et al, 2009a;Hughes et al, 2013b). However, the generation and propagation of action potentials is a dynamic process that not only results from increased excitation, but also loss of inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, little is known of how changes in the immune function aff ect the nerve function in IBS. Th is is despite the substantial body of work showing that luminal contents and infl ammatory mediators modulate intestinal nerve function in animal models, demonstrating that the function of these nerves remains altered long aft er resolution of the infl ammatory insult ( 4,5 ). Th is review focuses on how alterations in the immune system of IBS patients modulate GI nerve activity and symptoms.…”
Section: Introductionmentioning
confidence: 99%